ONLINE CONSUMER ANALYSIS OF INDONESIAN TRADITIONAL BATIK PRODUCTS - Hatane Semuel (Jurnal Manajemen dan Kewirausahaan, 2021)
This study aims to understand website user behavior and online shopping behavior intentions through website facilities and to address the problems of Indonesian traditional batik SMEs in carrying out online marketing. Web services are seen from the security, navigation capabilities, and visual appeal of the website. The study was conducted on 150 students and 96 SME batik owners who have positioned themselves as potential consumers. The respondents were asked to visit the Legendabatik.com website and then answer the questionnaire in the google form. The results found that all website facilities have a positive effect on intention to use, only visual appeal has a direct positive effect on online behavioral intentions, while intention to use has a strong positive influence on online behavioral intentions. So website management needs to prioritize the visual appeal to increase online shopping behavior intention